LA INTERRELACION DE LOS DOCENTES Y SU INFLUENCIA EN EL COMPORTAMIENTO DE LOS EDUCANDOS DE LA UNIDAD EDUCATIVA ''FRANCISCO HUERTA RENDON'' DE LA PARROQUIA CLEMENTE BAQUERIZO, CANTON BABAHOYO, PROVINCIA DE LOS RIOS DURANTE EL PERIODO 2011-2012. - MARGARITA FIGUEROA SILVA (2012)
THE INTERRELATIONSHIP OF TEACHERS AND ITS INFLUENCE ON THE BEHAVIOR OF THE STUDENTS OF THE ''FRANCISCO HUERTA RENDON'' EDUCATIONAL UNIT OF THE CLEMENTE BAQUERIZO PARISH, CANTON BABAHOYO, PROVINCE OF LOS RIOS DURING THE PERIOD 2011-2012.